Unexpected toxicity of very low dose MPTP in mice: A clue to the etiology of Parkinson's disease?. Issue 2 (1st December 2015) - Dovero, Sandra; Gross, Christian; Bezard, Erwan
ABSTRACT: Although much progress have been made in recent years, the etiology of idiopathic Parkinson's disease remains obscure. The chance discovery that injection of the neurotoxin 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) induces a syndrome very similar to parkinsonism introduced the "environmental toxin" hypothesis but no toxin was ever found in any quantity in patients' brains. We have unexpectedly now found, however, that, in mice, very low doses of MPTP induce as much dopaminergic neuronal death as far higher doses. Cellular detoxification mechanisms would appear to be incapacitated at such low doses. This could infer that the barely discernible presence of an unidentified neurotoxin may be responsible for the onset of Parkinson's disease.Synapse 70:49–51, 2016 . © 2015 Wiley Periodicals, Inc. Abstract : In mice, unusual very low doses of the pro‐parkinsonian neurotoxin MPTP induce as much dopaminergic neuronal death as far higher doses, infering that the barely discernible presence of an unidentified neurotoxin may be responsible for the onset of Parkinson's disease. The graph below indicates the number of tyrosine‐hydroxylase (TH) immunopositive neurons in the Substantia Nigra pars compacta (a marker of dopaminergic neurons) according to the cumulative MPTP dose given to mice.